The Effect of Peer Review on Students’ Motivation and Writing Ability - Susanto Susanto; Meiliana Hidayati (Center of Language and Cultural Studies [CLCS], 2020)
The objective of this research was aimed to investigate the effect of peer review on students’ motivation and ability in writing recount text. The method of the research was a quasi-experimental design with a control and experimental group and a post-test only. The population of this research was the entire eight grade students of SMPN 1 Tanggunggunung. The cluster random sampling was used in the sampling technique. There were two classes of eight grade students as the sample of this research. They were VIII D that consists of 32 students as the control class and VIII G that consists of 30 students as the experimental class. Tests and questionnaires were the instruments of this research. The data collected from the tests were analyzed by using independent sample t-test and MANOVA through SPSS. Results show that the independent sample t-test was 0.001 for motivation and 0.000 for the writing ability. Moreover, the result of the MANOVA test was 0.000. The results were consulted to the score of the significant value generated Sig. (P-value) < α = 0.05. Thus, Ho was rejected and Ha was accepted. In other words, the result of the study revealed that peer review gave a significant effect on the students’ motivation and ability in writing recount text. It can be concluded that there is a significant effect on the students’ writing motivation and writing ability who taught using peer review.